2016
DOI: 10.3389/fnins.2016.00490
|View full text |Cite
|
Sign up to set email alerts
|

Long Term Memory for Noise: Evidence of Robust Encoding of Very Short Temporal Acoustic Patterns

Abstract: Recent research has demonstrated that humans are able to implicitly encode and retain repeating patterns in meaningless auditory noise. Our study aimed at testing the robustness of long-term implicit recognition memory for these learned patterns. Participants performed a cyclic/non-cyclic discrimination task, during which they were presented with either 1-s cyclic noises (CNs) (the two halves of the noise were identical) or 1-s plain random noises (Ns). Among CNs and Ns presented once, target CNs were implicit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 26 publications
6
38
0
Order By: Relevance
“…Time-reversal would leave short-term power spectra unaffected, but would disrupt most cues based on timing. Viswanathan et al (2016) reported similar conclusions using time shuffling instead of time reversal. Finally, Andrillon et al (2015) observed sizeable EEG event-related potentials after learning.…”
Section: Introductionsupporting
confidence: 58%
See 2 more Smart Citations
“…Time-reversal would leave short-term power spectra unaffected, but would disrupt most cues based on timing. Viswanathan et al (2016) reported similar conclusions using time shuffling instead of time reversal. Finally, Andrillon et al (2015) observed sizeable EEG event-related potentials after learning.…”
Section: Introductionsupporting
confidence: 58%
“…In previous studies probing the acquisition of novel auditory memories, another type of random stimulus has been extensively used-white noise, obtained by drawing successive audio samples from a Gaussian distribution (Agus et al, 2010;Andrillon et al, 2015;Goossens et al, 2008;Guttman and Julesz, 1963;Kaernbach, 2004;Luo et al, 2013;Rajendran et al, 2016;Viswanathan et al, 2016;Warren et al, 2001). Studies of the memory for noise differed from each other in many experimental details, but, essentially, an exemplar of noise selected at random was presented to listeners more than once during an experiment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inspections of the nature of this memory revealed that it was robust to time reversal, and even to scrambling into bins as small as 10-20 ms (Agus, Thorpe, & Pressnitzer, 2010;Viswanathan, Rémy, Bacon-Macé, & Thorpe, 2016), indicating that the remembered features reflect local spectrotemporal idiosyncrasies within the reoccurring noise snippet. The apparent dependence of this memory on certain local features of the noise signal may also explain the high inter-sample variability often seen with this paradigm (i.e., the distinction between 'memorable' and 'not memorable' patterns; Agus et al, 2010;Viswanathan et al, 2016;Kang et al, 2017).…”
Section: Relationship To 'Noise Memory'mentioning
confidence: 99%
“…Agus et al . 148 demonstrated that human participants can rapidly learn to detect a particular token of repeated white noise and remember the same pattern for weeks 149 in a completely unsupervised fashion. Functional brain imaging experiments have implicated the auditory cortex as well as the hippocampus in encoding memory representations for such complex scenes.…”
Section: The Auditory Cortex and Learningmentioning
confidence: 99%